Growth Hormone Receptor Is a Target for Presenilin-dependent γ-Secretase Cleavage - Cowan, Jon W.; Wang, Xiangdong; Guan, Ran; He, Kai; Jiang, Jing; Baumann, Gerhard; Black, Roy A.; Wolfe, Michael S.; Frank, Stuart J. (The Journal of biological chemistry, 2005)
Growth hormone receptor (GHR) is a cytokine receptor superfamily member that binds growth hormone (GH) via its extracellular domain and signals via interaction of its cytoplasmic domain with JAK2 and other signaling molecules. GHR is a target for inducible metalloprotease-mediated cleavage in its perimembranous extracellular domain, a process that liberates the extracellular domain as the soluble GH-binding protein and leaves behind a cell-associated GHR remnant protein containing the transmembrane and cytoplasmic domains. GHR metalloproteolysis can be catalyzed by tumor necrosis factor-α-converting enzyme (ADAM-17) and is associated with down-modulation of GH signaling. We now study the fate of the GHR remnant protein. By anti-GHR cytoplasmic domain immunoblotting, we observed that the remnant induced in response to phorbol ester or platelet-derived growth factor has a reliable pattern of appearance and disappearance in both mouse preadipocytes endogenously expressing GHR and transfected fibroblasts expressing rabbit GHR. Lactacystin, a specific proteasome inhibitor, did not appreciably change the time course of remnant appearance or clearance but allowed detection of the GHR stub, a receptor fragment slightly smaller than the remnant but containing the C terminus of the remnant (receptor cytoplasmic domain). In contrast, MG132, another (less specific) proteasome inhibitor, strongly inhibited remnant clearance and prevented stub appearance. Inhibitors of γ-secretase, an aspartyl protease, also prevented the appearance of the stub, even in the presence of lactacystin, and concomitantly inhibited remnant clearance in the same fashion as MG132. In addition, mouse embryonic fibroblasts derived from presenilin 1 and 2 (PS1/2) knockouts recapitulated the γ-secretase inhibitor studies, as compared with their littermate controls (PS1/2 wild type). Confocal microscopy indicated that the GHR cytoplasmic domain became localized to the nucleus in a fashion dependent on PS1/2 activity. These data indicate that the GHR is subject to sequential proteolysis by metalloprotease and γ-secretase activities and may suggest GH-independent roles for the GHR.